Artemisia annua L.: produção de biomassa, artemisinina, rendimento e composição de óleo essencial em função de diferentes variedades e densidades de plantio - Capelin, Diogo (2012)
Artemisia annua L. is a herbaceous plant native from Asia which is much used as a source of essential oil and artemisinin, a sesquiterpene lactone used as antimalarial active principle. The search in the improvement regarding the production of A. annua is intense due to the high demand for this molecule. The aim of this study was to identify the suitable planting density for a higher yield of biomass, artemisinin and essential oil, and the composition of this, and also compare the performance of three varieties of A. annua for cultivation in the Southwest region of Paraná. In order to this, an experiment was conducted in a randomized block design with four replications. Three different varieties of A. annua were used: Artemis F2, and Artemis F1 (2/39 x 5)x3M. A second experiment was conducted with Artemis F2 variety in a randomized block design with three replications. The treatments were: T1: 16.666 plants ha-1, T2: 55.555 plants ha-1, T3: 94.444 plants ha-1 and T4: 133.333 plants ha-1. The plant material of both experiments was harvested at flowering (approximately 159 days after transplantation) and dried until a constant weight in an oven with air circulation at 35 ° C. The quantification of artemisinin was performed by thin-layer chromatography and detected by densitometry. The separation and quantification of substances present in the essential oil were performed by gas chromatography with a flame ionization detector and the identification of them was performed by gas chromatography coupled to a mass spectrometer. The results were submitted to analysis of variance and Tukey's test at 5% of failure probability for qualitative variables and the regression of the analysis of variance for quantitative treatments. All the tested varieties showed an increasing production in relation to the dry mass of the aerial part, dry mass of leaves, artemisinin and essential oil production per area and they did not differ statistically between themselves. The varieties of Artemis F1 and Artemis F2 had a higher leaf/stem ratio among the varieties tested. The varieties of Artemis F1 and (2/39 x 5)x3M showed a higher content of essential oil in the dry mass of leaves, and due to this they are recommended for cultivation in the Southwest region of Paraná, for the essential oil production. The main compounds found in essential oils from the three cultivars were camphor (39.69%), 1.8 cineole (12.66%), myrcene (9.29%), γ-muuroleno (4.95%), trans - β-farnesene (4.02%), which together totalize an average 70.61% of the essential oil of the varieties tested. Changes in the planting density had no significant influence on the major constituents regarding the essential oil of A. annua variety of Artemis F2. Concerning the different densities, the highest production of leaf biomass, artemisinin, artemisinin content in the dry mass of leaves and essential oil were obtained at densities of 93,966 plants ha-1, 80.0,71 plants ha-1, 81 969 plants ha-1 and 91,272 plants ha-1 respectively. The essential oil content in dry mass of leaves was not affected by the planting density. The alteration in planting density influenced the production of camphene, α-copaene, mirtenila acetate, γ-terpinene. Regarding all the planting densities, camphor was the major constituent with levels above 39% indicating that A. annua is an alternative source for the production of this substance. Monoterpenes were the most abundant class of compounds in essential oil of A. annua with 59.03% of the chemical constitution and 33.91% belong to the class of sesquiterpenes.